Implikasi Hukum Transaksi Jual Beli Tanah yang Tidak Melibatkan Pejabat Pembuat Akta Tanah (PPAT) - Sihombing, Pardamean; Sambuaga, Eddy; Napitupulu, Diana R.W (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
Land sale and purchase transactions are a form of land rights transfer that is legally regulated in Indonesian legislation, particularly in Government Regulation No. 24 of 1997 concerning Land Registration. One of the requirements for the validity of land rights transfer is the creation of a deed by a Land Deed Official (PPAT). However, in practice, there are still land sale and purchase transactions that do not involve a PPAT, which are only carried out privately between the parties. This study aims to analyze the legal implications of such transactions, both in terms of the validity of the transfer of rights, the strength of evidence, and the potential for legal disputes in the future. The research method used is normative juridical with a legislative approach and case studies. The results of the study show that land sale and purchase transactions that do not involve a PPAT do not have formal legal force to be registered with the land office, thus potentially causing legal uncertainty and ownership disputes. In addition, buyers are also in a vulnerable position because they do not have valid administrative proof of ownership. Therefore, the parties need to understand the applicable legal procedures so that land rights can be recognized and protected by law.